Solution of nonlinear integral equations via fixed point theorems in G-metric spaces - Rashwan, Rashwan; Saleh, Samera (International Journal of Applied Mathematical Research, 2014)
The main aim of this paper is to prove that the existence and uniqueness of solutions for systems of simultaneous Volterra Â Hammerstein and Urysohn nonlinear integral equations in G-metric spaces andÂ partially ordered G-metric spaces settings Â by using common fixed point theorems satisfying generalized contractive conditions.